Married by morning ebook - Kleypas, Lisa (Hathaways, 2010)
Married by Morning continues Lisa Kleypas's Hathaways beloved series set in Victorian London. For two years, Catherine Marks has been a paid companion to the Hathaway sisters—a pleasant position, with one caveat. Her charges' older brother, Leo Hathaway, is thoroughly exasperating. Cat can hardly believe that their constant arguing could mask a mutual attraction. But when one quarrel ends in a sudden kiss, Cat is shocked at her powerful response—and even more so when Leo proposes a dangerous liaison. Leo must marry and produce an heir within a year to save his family home. Catherine's respectable demeanor hides a secret that would utterly destroy her. But to Leo, Cat is intriguing and infernally tempting, even to a man resolved never to love again. The danger Cat tried to outrun is about to separate them forever—unless two wary lovers can find a way to banish the shadows and give in to their desires...